Fc gamma receptors: glycobiology and therapeutic prospects - Hayes JM; Wormald MR; Rudd PM; Davey GP (Dove Medical Press, 2016)
Jerrard M Hayes,1 Mark R Wormald,2 Pauline M Rudd,3 Gavin P Davey1 1School of Biochemistry and Immunology, Trinity Biomedical Sciences Institute, Trinity College, Dublin, Ireland; 2Department of Biochemistry, Oxford Glycobiology Institute, University of Oxford, Oxford, UK; 3NIBRT Glycoscience Group, National Institute for Bioprocessing, Research and Training, Dublin, Ireland Abstract: Therapeutic antibodies hold great promise for the treatment of cancer and autoimmune diseases, and developments in antibody–drug conjugates and bispecific antibodies continue to enhance treatment options for patients. Immunoglobulin (Ig) G antibodies are proteins with complex modifications, which have a significant impact on their function. The most important of these modifications is glycosylation, the addition of conserved glycans to the antibody Fc region, which is critical for its interaction with the immune system and induction of effector activities such as antibody-dependent cell cytotoxicity, complement activation and phagocytosis. Communication of IgG antibodies with the immune system is controlled and mediated by Fc gamma receptors (FcγRs), membrane-bound proteins, which relay the information sensed and gathered by antibodies to the immune system. These receptors are also glycoproteins and provide a link between the innate and adaptive immune systems. Recent information suggests that this receptor glycan modification is also important for the interaction with antibodies and downstream immune response. In this study, the current knowledge on FcγR glycosylation is discussed, and some insight into its role and influence on the interaction properties with IgG, particularly in the context of biotherapeutics, is provided. For the purpose of this study, other Fc receptors such as FcαR, FcεR or FcRn are not discussed extensively, as IgG-based antibodies are currently the only therapeutic antibody-based products on the market. In addition, FcγRs as therapeutics and therapeutic targets are discussed, and insight into and comment on the therapeutic aspects of receptor glycosylation are provided. Keywords: glycosylation, IgG, Fc gamma receptor, therapeutic monoclonal antibody